Analisis Kemampuan Berpikir Kritis Calon Guru Mi Pada Materi Bunyi Melalui Penggunaan Modul Berbasis STEM - Suci Nurmatin (Asatidzuna | Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Critical thinking skills are not only needed by students, but also needed by a prospectiveteacher. A prospective teacher who has good critical thinking skills should produce studentswho have good critical thinking skills as well. This study aims to analyze the critical thinkingskills of prospective MI teacher students. Seven students who took the basic concepts ofphysics course were used as participants. Data on the subject's critical thinking skills wereobtained based on the results of the evaluation using a STEM-based module. The results ofthe analysis of critical thinking skills show that prospective teachers have shown criticalthinking skills on sound material but have not been maximized